2021
DOI: 10.3390/ijms22168929
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuroinflammation and Blood-Brain Barrier Permutability on Migraine

Abstract: Currently, migraine is treated mainly by targeting calcitonin gene-related peptides, although the efficacy of this method is limited and new treatment strategies are desired. Neuroinflammation has been implicated in the pathogenesis of migraine. In patients with migraine, peripheral levels of pro-inflammatory cytokines, such as interleukin-1β (IL-1β) and tumor necrosis factor-α, are known to be increased. Additionally, animal models of headache have demonstrated that immunological responses associated with cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 120 publications
1
27
0
Order By: Relevance
“…However, due to the limited access of IgG antibodies to central sites within the BBB, an effective central effect of CGRP-targeting antibodies appears unlikely. Moreover, despite some controversial clinical observations, no convincing evidence supports the assumption that migraine attacks enhance the permeability of the BBB, allowing the passage of chemical substances from the blood into the brain tissue [ 75 ]. Therefore, trigeminal ganglion neurons and satellite cells and the dura mater innervated by the peripheral axons of the trigeminal afferents—structures not protected by the BBB—are the most likely targets of the antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the limited access of IgG antibodies to central sites within the BBB, an effective central effect of CGRP-targeting antibodies appears unlikely. Moreover, despite some controversial clinical observations, no convincing evidence supports the assumption that migraine attacks enhance the permeability of the BBB, allowing the passage of chemical substances from the blood into the brain tissue [ 75 ]. Therefore, trigeminal ganglion neurons and satellite cells and the dura mater innervated by the peripheral axons of the trigeminal afferents—structures not protected by the BBB—are the most likely targets of the antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory nerve fibers contain neuropeptides coming from the trigeminal ganglion (TG) that innervate the dura, generating neurogenic inflammation in the dura. The direct conduction of TG neurons can activate c-fos in the TNC, resulting in a pain sensation that is eventually experienced as a headache ( 77 ). Furthermore, evidence from mice and rat studies showed that parenchymal neuroinflammatory signaling between neurons, astrocytes, and microglia, which finally migrates to the meninges ( 65 , 66 , 78 , 80 85 ), might be the potential pathway of transferring a non-homeostatic activity in the unconscious brain to pain-sensitive meninges ( 86 , 87 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our data demonstrated that saracatinib reduced IL-1β, CCL2, and CXCL1 release promoted by CGRP in the TG ( Figure 3 A–C). All these proteins are associated with pain hypersensitivity and migraine [ 61 , 62 , 63 , 64 , 65 ]. We therefore further investigated whether SFKs activity promotes cytokines production machinery by examining the effect of the SFKs inhibitor saracatinib on their CGRP-induced gene expression.…”
Section: Resultsmentioning
confidence: 99%